1998
DOI: 10.1037/0022-3514.75.4.887
|View full text |Cite
|
Sign up to set email alerts
|

Negative information weighs more heavily on the brain: The negativity bias in evaluative categorizations.

Abstract: Negative information tends to influence evaluations more strongly than comparably extreme positive information. To test whether this negativity bias operates at the evaluative categorization stage, the authors recorded event-related brain potentials (ERPs), which are more sensitive to the evaluative categorization than the response output stage, as participants viewed positive, negative, and neutral pictures. Results revealed larger amplitude late positive brain potentials during the evaluative categorization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

129
930
15
10

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,295 publications
(1,103 citation statements)
references
References 43 publications
129
930
15
10
Order By: Relevance
“…Carver and Vaccaro's results indicate that infants allocated greater attention to the toy associated with a negative emotion than to the toys associated with positive or neutral emotions. These results parallel the finding by Ito, Larsen et al (1998;see introduction) that adults' ERPs show enhanced activity in response to evaluatively negative as compared to positive or neutral stimuli.…”
Section: A Evidence From Social Referencingsupporting
confidence: 88%
“…Carver and Vaccaro's results indicate that infants allocated greater attention to the toy associated with a negative emotion than to the toys associated with positive or neutral emotions. These results parallel the finding by Ito, Larsen et al (1998;see introduction) that adults' ERPs show enhanced activity in response to evaluatively negative as compared to positive or neutral stimuli.…”
Section: A Evidence From Social Referencingsupporting
confidence: 88%
“…Along this line of thought high affording tools facilitate the activation of motor schemata as indexed by the reduction in N300. Furthermore, previous electrophysiological research on esthetic evaluation which required explicit judgments (Jacobsen and Höfel, 2003) revealed that between 300 and 400 ms a fronto-central phasic negativity, more pronounced for non-beautiful patterns, may reflect a greater responsivity to negative than positive stimuli during the explicit evaluation processes (Ito et al, 1998;Jacobsen and Höfel, 2003;Höfel et al, 2007). Taking this previous evidence into account, our results suggest that both affordance and attractiveness work together to facilitate the tool recognition processes in the recoverability of the object representation when the tool is both high affording and high attractive.…”
Section: Discussionmentioning
confidence: 96%
“…From the field of emotion research it has been theorized that slow positive waves such as the P3 and related LPPs are an index of motivational relevance (Ito et al 1998;Schupp et al 2000Schupp et al , 2006. Stimulus-related late positive peaks in the ERP reflect perceptual processing of the stimulus, which is strongly driven by motivational relevance of the stimulus (Junghöfer et al 2006).…”
Section: Introductionmentioning
confidence: 99%